Autophagy and exosome dynamics in Radiation-Induced pulmonary fibrosis: the critical role of TRIB3 - Na Li; Wenyue Zhao; Jiale Li; Dengfeng Zhang; Kejun Li; Mengmeng Yang; Xinran Lu; Liqing Du; Chang Xu; Qiang Liu (Respiratory Research)
Abstract Objective Dysregulated autophagy plays a critical role in the pathogenesis of pulmonary fibrosis. The stress protein TRIB3 has been correlated with abnormal autophagy, but its specific contribution to radiation-induced pulmonary fibrosis (RIPF) remains unclear. This study aimed to elucidate the role of TRIB3 in RIPF progression. Methods We conducted RNA-sequencing of rat RIPF lung tissue to analyze the transcriptomic profile and determine gene expression changes in murine with RIPF. We established mouse models with alveolar epithelial type II cells (AEC II)-specific knockdown or overexpression of TRIB3 to elucidate its role in RIPF progression. We utilized mRFP-GFP-LC3 fluorescent reporter cells, nanoparticle tracking analysis, immunofluorescence and immunoprecipitation assays to uncover the underlying mechanisms. Results TRIB3 expression was elevated in irradiated AEC II. Silencing TRIB3 in AEC II mitigated RIPF in mice, whereas its overexpression exacerbated the condition. Mechanistically, TRIB3 interacted with the LC3-interacting region (LIR) motif and ubiquitin-associated (UBA) domain of sequestosome 1 (SQSTM1), an autophagic receptor protein, thereby inhibiting autophagic flux in AEC II cell line MLE12. This inhibition increased exosome secretion and facilitated crosstalk between MLE12 cells and fibroblasts, ultimately enhancing the proliferation and extracellular matrix production of lung fibroblasts. Conclusion TRIB3 in AEC II inhibits autophagic flux by interacting with SQSTM1, thereby increasing exosome secretion, which promotes fibroblast proliferation and extracellular matrix production, contributing to RIPF progression.